Finding and Counting Difficult to Reach Population Groups in the UK (and other Developed Countries) - Roy Carr-Hill (International Journal of Population Data Science, 2018)
Background Censuses are meant to provide a complete count and basic information about all households and individuals in a country. After decades of complacency, it has begun to be realised that this can no longer be guaranteed. Several of the presentations at the Edinburgh in March 2018 demonstrated methods which the ONS were developing to resolve many of the problems; but those methods do not solve the problem of those who, for a variety of reasons, cannot or do not want to be counted.